2019
DOI: 10.1038/s41405-018-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception about dental implants among undergraduate dental students

Abstract: IntroductionAwareness about dental implants is increasing among dental patients, which demands a higher level of competence for dental students. So, the objective of this study was to assess the knowledge and perception of undergraduate dental students about dental implants.Materials and methodsThis cross-sectional questionnaire-based survey was conducted after taking ethical clearance and approval from the Institutional Review Committee of B.P. Koirala Institute of Health Sciences and informed consent from ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 18 publications
0
34
2
Order By: Relevance
“…The predominance of males over females was also reported in a previous study, which attributed this finding to other factors, stating that the dental profession worldwide is generally more male dominated [ 31 ]. However, this finding is inconsistent with other studies [ 32 – 35 ]. One of these studies, which was conducted in India, attributed this shift to the growing increase in females over males that has occurred over several years [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The predominance of males over females was also reported in a previous study, which attributed this finding to other factors, stating that the dental profession worldwide is generally more male dominated [ 31 ]. However, this finding is inconsistent with other studies [ 32 – 35 ]. One of these studies, which was conducted in India, attributed this shift to the growing increase in females over males that has occurred over several years [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Sharma and his colleagues also found a higher number of female students in the 5th year and 4th year among the students who participated in their survey. Moreover, the researchers noted that even in the late-clinical year, a majority of students gave unsatisfactory answers [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral hygiene behaviours were evaluated using five items adapted from the Turkish version of HU-DBI (items no. 1, 4, 9, 12, and 16) [ 29 , 36 ]. While 243 (63.1%) participants reported that they do not worry about visiting the dentist, only 29 (7.5%) and 50 (13%) of them had used disclosing dye and a child-sized toothbrush.…”
Section: Resultsmentioning
confidence: 99%
“…A study given by Arati Sharma, et. al;(Sharma et al, 2019, found that a majority of the total students perceived themselves to be moderately well informed about dental implants (54.6%). Awareness about dental implants is increasing among dental patients, which demands a higher level of competence for dental students.…”
Section: Resultsmentioning
confidence: 96%